Monoclonal Antibodies against Beta-2-Glycoprotein I: Use as Reference Material for Lupus Anticoagulant Tests - Arnout, J.; Vanrusselt, M.; Wittevrongel, C.; Vermylen, J. (Thrombosis and Haemostasis, 1998)
The laboratory diagnosis of lupus anticoagulants (LA) remains difficult despite internationally accepted guidelines for its detection. Several interlaboratory surveys have shown poor agreement between laboratories. Further standardization of LA testing will to a large extent depend on better insights on the mechanisms by which LA affect phospholipid-dependent coagulation assays as well as on the availability of well characterized and internationally accepted reference materials and control specimens. We recently raised a series of murine monoclonal antibodies against human β2GPI (anti-β2GPI moabs), a phospholipid-binding protein directly involved in the interaction between certain lupus anticoagulants and phospholipids. In this study we report on the use of LA positive anti-β2GPI moabs as easy to handle reference and control material. The relative LA responsiveness of various phospholipid-dependent clotting assays was determined on plasmas spiked with such moabs and compared well with that determined on LA positive plasma samples. Plasmas spiked with LA positive anti-β2GPI moabs were also used as control specimens to study the interlaboratory precision of LA testing. With these control specimens, low interassay coefficients of variation were obtained. Our results indicate that LA positive anti-β2GPI moabs have potential for the production of control specimens that could be made available to routine hemostasis laboratories to assess intra-laboratory precision of LA testing and to manufacturers to control batch-to-batch variability of their reagents.